Phenotypic and genetic variation of Jatropha curcas L populations from different countries - Biabanikhanehkahdani, Alireza; Yusop, Mohd Rafii; Saleh, Ghizan; Shabanimofrad, Mahmoodreza; Latif, Md Abdul (Consiglio per la ricerca in agricoltura e l'analisi dell'economia agraria, 2012)
Jatropha populations from Malaysia, India, Indonesia, and the Philippines were evaluated on inland soils at University Agriculture Park, Universiti Putra Malaysia with the main objectives are to select superior plants with high seed and oil yields production for commercial planting and to study inter-populations variation in morphological, seed and oil yields characteristics. Analysis of variance shows that all traits had significant variation among populations. Phenotypic correlations between seed yield per plant was positively and highly significantly correlated with days to flowering, number of inflorescences, number of fruits per plant, number of seeds per plant, seed yield per hectare, seed oil yield per plant, and seed oil yield per hectare. Seed yield per plant was highly significant negatively correlated with seed oil content. Cluster analysis based on standardized agro-morphological data, divided the Jatropha populations into three clusters through non-hierarchical clustering. Cluster I, II, III consisted of one, two and three populations respectively. Highly significant genotypic differences were obtained among the Jatropha populations for various traits measured. The relative large variations were observed for all traits except number of tertiary branches in first year of harvesting. The variation was large enough to suggest that six Jatropha populations could present appropriate genotypes to be used in intensive breeding programs.